Targeting agricultural extension efforts through a typological analysis for potato small farmers in the Northern Andes of Peru - Ramírez, D.; Ninanya, J.; Rinza, J.; Briceño, P.; Otiniano, R. (International Potato Center, 2023)
Agricultural extension work is crucial for rural development to guarantee technology dissemination and productivity, especially for small farmers. However, small farmers' requirements are context-specific, and characterization of these requirements is necessary to ensure a successful extension effort. This study encompasses a typological analysis of small farmers from a potato-based system in the Northern Andes of Peru. The agronomic data log of 608 potato farmers from the e-Agrology platform was analyzed for the period of April 2021 to June 2022. After data cleaning and recategorization, a multiple correspondence analysis was conducted followed by a hierarchical clustering analysis. Improved seed type (26.1%), not certified seed category (18.8%), planting type by paid workers (16.8%), and female gender (22.8%) were the most critical contributing variables to components 1, 2, 3, and 4, respectively, which explained about 29% of the cumulative variance. Three typologies were defined including “business as usual” (I); “risky” (II); and “progressive” (III) behaviors in potato cultivation. Typology I cultivated in the main growing period using common varieties in communal lands and using traditional methods. Typology II cultivated potatoes in the secondary growing period in small plots based on market demand. Typology III cultivated in the primary growing period using uncommon varieties and improved seeds in communal lands. Target actions including climatic advisory, market information access, seed systems improvement, etc., for extension purposes were identified for each typology to improve potato production in the area.